بن يوسف بن خدة و مواقفه من القضايا الوطنية من خلال مؤلفاته 1920-2003م - مريم قريد; د/محمد عطية (جامعة عمار ثليجي الاغواط, 2025)
الملخص يُعد بن يوسف بن خدة من أبرز رموز النضال الوطني الجزائري، إذ كرّس حياته لخدمة قضية التحرير متسلحًا بثقافة رصينة وذكاء سياسي واستقامة أخلاقية. وُلد في بيئة محافظة ومثقفة، وتكوّن وعيه الوطني في سن مبكرة نتيجة الظلم الاستعماري الذي شهده في المدرسة والمجتمع، مما دفعه إلى الانخراط في الكشافة الإسلامية، ثم في حزب الشعب وجبهة التحرير الوطني. برز نشاطه السياسي في التعليم الثانوي، وتدرج في المناصب حتى أصبح أمينًا عامًا لحزب الشعب، حيث واجه تحديات كبيرة، أبرزها الخلاف مع مصالي الحاج، مما ساهم في تمهيد الطريق لثورة نوفمبر 1954. كما كان له دور محوري في مفاوضات الاستقلال، واعتبر اتفاقيات إيفيان انتصارًا حقيقيًا للشعب الجزائري، حافظ من خلالها على وحدة الجزائر الترابية رغم محاولات فرنسا الالتفافية، خاصة فيما يتعلق بالصحراء. Abstract: Ben Youssef Benkhedda is considered one of the most prominent figures of the Algerian national struggle, having dedicated his life to serving the cause of liberation, armed with a solid culture, political intelligence, and moral integrity. Born into a conservative, cultured environment, his national consciousness was formed at an early age as a result of the colonial injustice he witnessed at school and in society. This led him to join the Islamic Scouts, and later the People's Party and the National Liberation Front. His political activity became prominent in secondary school, and he rose through the ranks until he became Secretary-General of the People's Party, where he faced significant challenges, most notably the dispute with Messali Hadj, which contributed to paving the way for the November 1954 Revolution. He also played a pivotal role in the independence negotiations and considered the Evian Accords a true victory for the Algerian people, through which he preserved Algeria's territorial integrity despite France's attempts to circumvent it, particularly with regard to the Sahara.